2012
DOI: 10.1073/pnas.1200037109
|View full text |Cite
|
Sign up to set email alerts
|

Identification of benzodiazepine Ro5-3335 as an inhibitor of CBF leukemia through quantitative high throughput screen against RUNX1–CBFβ interaction

Abstract: Core binding factor (CBF) leukemias, those with translocations or inversions that affect transcription factor genes RUNX1 or CBFB, account for ∼24% of adult acute myeloid leukemia (AML) and 25% of pediatric acute lymphocytic leukemia (ALL). Current treatments for CBF leukemias are associated with significant morbidity and mortality, with a 5-y survival rate of ∼50%. We hypothesize that the interaction between RUNX1 and CBFβ is critical for CBF leukemia and can be targeted for drug development. We developed hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 42 publications
4
120
1
Order By: Relevance
“…CBF␤ was previously known as a transcriptional cofactor regulating the DNA binding capacity of RUNX1 (61). In addition, RUNX1 and CBF␤ were found to synergistically inhibit Tat-mediated HIV-1 long terminal repeat (LTR) transactivation (52). However, our data rule out a role of CBF␤ in the transcriptional regulation of Vif expression.…”
Section: Discussioncontrasting
confidence: 53%
“…CBF␤ was previously known as a transcriptional cofactor regulating the DNA binding capacity of RUNX1 (61). In addition, RUNX1 and CBF␤ were found to synergistically inhibit Tat-mediated HIV-1 long terminal repeat (LTR) transactivation (52). However, our data rule out a role of CBF␤ in the transcriptional regulation of Vif expression.…”
Section: Discussioncontrasting
confidence: 53%
“…Next, we assessed the effect of a recently reported RUNX1 inhibitor, Ro5-3335, on the growth of MLL-AF9 cells (31). We confirmed an inhibitory effect of Ro5-3335 on human RUNX1 and RUNX2 using a CB cell culture assay (Supplemental Figure 6, B and C).…”
Section: Introductionmentioning
confidence: 51%
“…Recent efforts to target this transcription factor complex in CBF leukemia (31) should be extended to AML associated with MLL rearrangements and potentially to other myeloid neoplasms with RUNX1 dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, inhibition of RUNX1, either through short hairpin RNA knockdown or a RUNX1 chemical inhibitor, Ro5-3335, 184 suppressed leukemia development by MLL-AF9 in a mouse model. They also found that additional MLL fusion genes require RUNX1 for leukemogenesis.…”
Section: Requirement Of Normal Runx1 For Leukemogenesismentioning
confidence: 99%